EXPERIMENTAL STUDY OF N-(γ-AMINOBUTYRYL)-1-AZA-4,7,10,13-TETRAOXACYCLOPENTADECANE HYDROCHLORIDE ANALGESIC ACTIVITY IN PAIN SYNDROMES OF DIFFERENT ETIOLOGY - Voloshchuk, N.I.; Orlenko, O.B.; Petrushenko, V.V.; Basok, S.S.; Larionov, V.B.; Golovenko, M.Ya. (World of Medicine and Biology, 2024)
The pharmacotherapy of pain syndrome remains a significant and pressing medical issue. Therefore, scientists from various medical, pharmaceutical, and chemical specialties are working towards a solution. The study investigated the analgesic activity of N-(γ-aminobutyril)-1-aza-4,7,10,13-tetraoxacyclopentadecane hydrochloride (gabalgin), a new original compound, on laboratory animals. The severity and duration of the analgesic activity were evaluated using the “hot plate”, “tail flick”, “acetic writhing test”, and the neuropathic pain model, which was reproduced by ligation of the sciatic nerve in rats. The test compound was administered intraperitoneally at a dose of 3 mg/kg. The study found that gabalgin exhibits significant analgesic activity in all pain perception models, with comparable or superior strength to the comparison drugs ketorolac, gabapentin, and diclofenac. Additionally, gabalgin's antinociceptive effect lasts longer than diclofenac.
Keywords: analgesic activity; GABA derivatives; crown ether; neuropathic; somatic; thermal pain syndromes; experiment; rats; mice